2014
DOI: 10.1177/0956462413517670
|View full text |Cite
|
Sign up to set email alerts
|

Posterior reversible encephalopathy syndrome in disseminated histoplasmosis and advanced HIV infection

Abstract: The cause of posterior reversible encephalopathy syndrome (PRES) is often multifactorial. It is uncommon in patients with human immunodeficiency virus (HIV) infection. However, if the cause of PRES is left untreated it can cause significant morbidity and mortality. Thus, we believe it should be included as a differential in immunosuppressed patients presenting with neurological signs. This case report describes such a patient with acquired immunodeficiency syndrome (AIDS) who developed hypocalcaemia secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…No classical risk factors for PRES were present. In contrast to the cases of HIV-infected patients with PRES published so far, 11–15 our patient suffered neither from advanced immunodeficiency nor from opportunistic infection. However, it is conceivable that the impaired cerebrovascular reactivity, which persists even in treated and virally suppressed HIV₋infected individuals, and the persistent immune activation in these patients may represent an undetected risk factor for the development of PRES.…”
Section: Introductioncontrasting
confidence: 99%
“…No classical risk factors for PRES were present. In contrast to the cases of HIV-infected patients with PRES published so far, 11–15 our patient suffered neither from advanced immunodeficiency nor from opportunistic infection. However, it is conceivable that the impaired cerebrovascular reactivity, which persists even in treated and virally suppressed HIV₋infected individuals, and the persistent immune activation in these patients may represent an undetected risk factor for the development of PRES.…”
Section: Introductioncontrasting
confidence: 99%
“…However, there were several studies that found that PRES is related to human immunodeficiency virus (HIV) (53)(54)(55). A low incidence of pediatric PRES patients (1.5%) after HSCT with immunodeficiency was found by Zama et al (27) in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports in the literature describe PRES in HIV-infected patients, most often in those with advanced immunodeficiency, though it has been rarely described in patients with well-controlled HIV. 22 , 23 , 24 , 25 Possible mechanisms include impaired cerebrovascular reactivity even in virally suppressed patients and long-term exposure to antiretroviral therapies that may lead to mitochondrial damage in endothelial cells. 25 The HIV-infected patient presented here had a CSF profile with elevated protein and neutrophilic pleocytosis.…”
Section: Discussionmentioning
confidence: 99%